A repercuss??o das unidades de assist??ncia m??dica ambulatorial (AMA) no munic??pio de S??o Paulo sobre a demanda na rede de aten????o em sa??de p??blica - Pissinato, Adriana Vieira da Silva (2014)
Medical Assistance Ambulatory (AMA) was the strategy created by the city of S??o Paulo to fix the problem from the spontaneous demand coming from basic health units (UBS) and emergency rooms (PS). AMA routine from 2005 to 2013 has been the target of discussions that leave its work proposal questionable, which leads to the need of study and understanding of its impact on demand and Health Care net. The aim of this research was to conduct an analysis of the distribution of demand for medical care provided in the AMA, UBS and PS in S??o Paulo; especially in Freguesia do ?? and Brasil??ndia Regional Administration of Health. This exploratory and descriptive study using the data from SIA ??? Datasus, medical records and medical reports about the distribution of demand through the number of medical consultations of AMA Services to analyze the profile of patients using the AMA and how they are inserted in the Health Care net. It was observed that from 2002 to 2013 there was a reduction of 30% of visits made by UBS (Basic Health Unit), increase and subsequent stabilization of medical care provided by the AMA and initial reduction (2005) and subsequent increase (2011) in the number of assistance in PS (emergency room). This was also observed in the STS Freguesia do ?? / Brasil??ndia. Were analyzed 156 medical records, it was notice that 91.7% of patients were treated at the AMA conform the objectives of this device. However, 81.4% of these patients require medical monitoring, and 22% are not accompanied. Considering the ordinance 1101 / MS 2011, 85% of patients had access to more than 2 visits / year in AMA and 71.2% of patients at 1 medical consultation / year at UBS. It was concluded that the AMA increased the supply of consultations in S??o Paulo and favored the patient's access to the health system. However, the poor articulation of health care net associated with lack of knowledge of the patients about the health devices affects the promotion and health monitoring. This study subsidied the analysis of health system in S??o Paulo city before and after Ama inclusion in the Health Care net and encourage new studies to be conducted on this topic.